Dialog dan Kerukunan Antar Umat Beragama - Khotimah Khotimah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
To reach religious harmony, each religious follower should understand his own religion and respect religious diversity. In a theoretical study, to appreciate religious diversity and religious differences, there are at least three approaches always used: theological, political, and socio-cultural approach. Furthermore, there are some basic principles implemented in an interreligious dialogue. These principles could be from the norms of each religion or from personal experience of the religious follower either a direct experience or an experience based on understanding the phenomena of religious practices.